Analgesic effects of the novel semicarbazide-sensitive amine oxidase inhibitor SZV 1287 in mouse pain models with neuropathic mechanisms: Involvement of transient receptor potential vanilloid 1 and ankyrin 1 receptors. (May 2018) - Horváth, Ádám; Tékus, Valéria; Bencze, Noémi; Szentes, Nikolett; Scheich, Bálint; Bölcskei, Kata; Szőke, Éva; Mócsai, Attila; Tóth-Sarudy, Éva; Mátyus, Péter; Pintér, Erika; Helyes, Zsuzsanna
Graphical abstract: Abstract: Semicarbazide-sensitive amine oxidase (SSAO) produces tissue irritants by deamination of primary amines, which activate transient receptor potential ankyrin 1 (TRPA1) and vanilloid 1 (TRPV1) receptors expressed predominantly on nociceptors. Since there are no data about its functions in pain, we studied the effects and mechanisms of action of our novel SSAO inhibitor and dual TRPA1/TRPV1 antagonist multi-target drug SZV 1287 in different pain models. Acute chemonociception was induced by TRPV1 and TRPA1 activation (resiniferatoxin and formalin, respectively), chronic arthritis by K/BxN serum transfer, traumatic mononeuropathy by sciatic nerve ligation. SZV 1287 (20 mg/kg i.p.) was investigated in C57BL/6J wildtype (WT), TRPA1- (TRPA1 −/− ) and TRPV1-deficient (TRPV1 −/− ) mice. Paw mechanonociception was measured by aesthesiometry, thermonociception by hot plate, nocifensive behavior by licking duration, volume by plethysmometry, myeloperoxidase activity by luminescence and plasma extravasation by fluorescence imaging, glia activation in pain-related brain regions by immunohistochemistry. SZV 1287 significantly inhibited both TRPA1 and TRPV1 activation-induced acute chemonociception and hyperalgesia. In K/BxN arthritis, daily SZV 1287 injections significantly decreased hyperalgesia, L4-L6 spinal dorsal horn microgliosis, edema and myeloperoxidase activity. SZV 1287-evoked antihyperalgesic and anti-edema effects were absent in TRPV1 −/−, and remarkably reduced in TRPA1 −/− mice. In contrast, myeloperoxidase-inhibitory effect was absent in TRPA1 −/−, but not in TRPV1 −/− animals. Acute SZV 1287 administration resulted in approximately 50% significant reduction of neuropathic hyperalgesia 7 days after nerve ligation, which was not observed in either TRPA1 −/− or TRPV1 −/− mice. SZV 1287 inhibits chronic inflammatory and neuropathic pain via TRPV1 and TRPA1/TRPV1 activation, respectively, highlighting its drug developmental potential.